dôNrm'-lä-püsl - Edwards, Kari (Book collections on Project MUSE., 2017)
There have been many iterations of the Joan of Arc story: "testimonies," books, and films have attempted to capture the drama of one of history's most famous gender warriors. But few, if any, have been undertaken by an author who met her subject matter with such recognition and insight, a fellow warrior, a rebel in kind. kari edwards, a transgender activist and key figure in the Bay Area experimental writing scene of the late 1990s and early 2000s, was provocative and prescient in her concern for the way that language inflects, inflicts, and regulates gender norms. Her persistent efforts to break linguistic binaries and barriers have given her texts an ongoing urgency after her untimely death in 2006. This book brings to life an important document discovered in the late poet's archive at the Poetry Collection at the University of Buffalo. The several notebooks and partial typescript (as well as various plans and notes) of edwards' unfinished dôNrm'-lä-püsl, uncovered by Tina Žigon, offer an intriguing glimpse of a major new direction in edwards' work, one in which her avant-garde instincts are channeled through rigorous research on this medieval figure. In this retelling - better to say "remixing" - of Joan of Arc's fateful trial and martyrdom, we find the major theme so richly laced throughout edwards' oeuvre: the courageous (but also depressingly mundane) struggle against the stifling regulation of language, appearance, and norms. edwards's Joan of Arc, even in its incomplete and abbreviated form (which Žigon calls a "possible version" of edwards's manuscript), offers an exciting engagement with one of the medieval period's most challenging and mysterious figures.